2020
DOI: 10.3390/antibiotics9090594
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of the Alternative Use to Antibiotics in Poultry Production: An African Perspective

Abstract: Over the years the growth and health of food-producing animals have been enhanced by the use of antibiotics. These have helped reduce on-farm mortalities, lower incidences of diseases and more importantly improve productivity. Generally, the utilization of antibiotics in feed has been reevaluated since bacterial pathogens have established and shared a variety of antibiotic resistance mechanisms that can easily be spread within microbial communities. Multiple countries have introduced bans or severe restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 95 publications
(84 reference statements)
0
29
0
Order By: Relevance
“…These should include policies and regulations on prescription practices, animal feed, surveillance of antimicrobial resistance and antimicrobial use, antimicrobial disposal, and strengthening the national drug regulatory authorities in the agriculture, human and animal health sectors. These policies should include the banning of over-the-counter sales and restrictions of non-therapeutic uses of antibiotics, while promoting alternatives to antibiotics such as probiotics, prebiotics and phytobiotics [ 157 ]. Already, Namibia has introduced a ban on the routine use of antibiotics in healthy animals [ 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…These should include policies and regulations on prescription practices, animal feed, surveillance of antimicrobial resistance and antimicrobial use, antimicrobial disposal, and strengthening the national drug regulatory authorities in the agriculture, human and animal health sectors. These policies should include the banning of over-the-counter sales and restrictions of non-therapeutic uses of antibiotics, while promoting alternatives to antibiotics such as probiotics, prebiotics and phytobiotics [ 157 ]. Already, Namibia has introduced a ban on the routine use of antibiotics in healthy animals [ 158 ].…”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of antibiotics in animal husbandry is considered an important contributor to microbial resistance, as antibiotics are not only used in treatment of developed infection but also as a growth promotor factor or prophylactic, often administered to an entire stock of animals [ 93 , 94 ]. Manure and other animal waste, as well as wastewater from farms, could be contaminated with antibiotics, their metabolites and resistant strains of bacteria [ 95 , 96 , 97 ]. Their improper disposal could also contaminate food sources, further propagating their resistance [ 96 , 98 , 99 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
“…Manure and other animal waste, as well as wastewater from farms, could be contaminated with antibiotics, their metabolites and resistant strains of bacteria [ 95 , 96 , 97 ]. Their improper disposal could also contaminate food sources, further propagating their resistance [ 96 , 98 , 99 ]. A survey found that roughly half of Italian veterinarians working on pig and cattle farms considered antimicrobial usage as not always in line with the guidelines [ 100 ].…”
Section: Antimicrobial Stewardship In Community Pharmacymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the global consumption of antimicrobials in food animal production is anticipated to increase by two-thirds by 2030 due to rises in production and the demand for animal products. [ 129 ] Although most antibiotic use occurs in the agricultural sector, relatively little research has been done on how antibiotic use in food animals contributes to the overall problem of antibiotic resistance. There is a notable lack of quantitative monitoring data on antibiotic use in broilers in most large poultry-producing countries [ 40 ].…”
Section: Research Gap Status and Future Trendsmentioning
confidence: 99%